Modeling of real pH Neutralization Process using Multiple Neural Networks (MNN) Combination Technique. - Ahmad, Zainal; Roslin, Fairuoze (2007)

(untitled)
Combining multiple neural networks appears to be a very promising approach in improving neural network generalisation since it is very difficult, if not impossible, to develop a perfect single neural network (SNN) especially when dealing with a real time data.